Concepções de aprendizagem em organizações criativas: um estudo em companhias cearenses de dança - Queiroz, Laane Lima (2015)
This work has as main objective to analyze the learning concepts in dance companies in Ceará. For this, the following specific objectives were established: 1) to investigate the learning reference in dance companies in Ceará; 2) to analyze the learning process in dance companies in Ceará; 3) to describe the learning contexts in dance companies in Ceará; and 4) to identify the factors that influence learning in dance companies in Ceará. Were used as theoretical reference the learning concepts proposed by Basto (2013) and factors that influence learning by Caldeira and Godoy (2011). In the methodological aspects, the study of a mixed nature; exploratory-descriptive; documentary and field through the study of multiple case in four dance companies in Ceará: Dita Company and Company Vata, in Fortaleza; Paracuru Company of Dance, in Paracuru; and, the Company Ballet Baião of contemporary dance in Itapipoca. Semi-structured interviews were conducted with nine dance professionals and questionnaire built in Likert scale with 24 respondents. Data analysis followed the steps of content analysis for qualitative data and the use of SPSS version 21 for treatment of quantitative data. The results indicated that learning reference converges with the theoretical concept of Senge (1990; 2003) by linking learning with personal development, the influence of mental models of each individual, to share goals, the group work and systems thinking; and Kolb (1984) by relating the generation of knowledge through experience. As for the process of learning the sequence of six steps was found: identification; observation; reflection; memory; implementation and sharing. It was confirmed that the learning contexts in dance companies in Ceará will still begin in childhood, being improved in educational institutions in dance from the integration with professional dancers. Finally, the questionnaires showed high level of agreement with the following factors that influence learning: tolerance to errors (66.7%); equal power and responsibility (83.3%); involvement (95.8%); encouraging change and innovation (75%); systemic vision that includes sharing (58.3%) and external interaction (87.5%); effective communication (75%), decentralized organizational structure (54.2%) and effective leadership (62.5%). Thus, it is concluded that the present study is as a contribution to the development of knowledge about learning concepts in creative organizations.